THE COMPETENCY ANALYSIS OF PRINCIPAL AGAINST TEACHERS IN CONDUCTING DISTANCE LEARNING IN COVID-19 PANDEMIC - Elfrianto Elfrianto; Irfan Dahnial; Bahdin Nur Tanjung (UIN Sumatera Utara Medan, 2020)
This study aims to analyze the principal's competence towards teachers implementing online learning during the 19th period to save the vital role of education itself, especially the opportunity for the principal as a leader in the school environment to give influence to the teacher in the distance learning process (online), as well as providing safety for many people, especially for students to avoid covid19. This study is a study that uses a literature review method that is where the authors make observations and reviews as well as analyzing the results of previous writings that will become a reference in this writing. The results of this study are: 1) the role of the principal is vital in term of the competencies that must be possessed by a leader in the school environment not only during the COVID-19 pandemic but also during ordinary situations; 2) and during such regular activities, the role and Principal competence must be able to provide positive space for teachers to improve competence in term of teaching and learning.